On Subtractive Derivations of Rl-Monoids. (18th February 2023) - Gao, Yu; Li, Bingfang
Abstract : This paper is intended to introduce the subtractive derivations and study some of their algebraic properties on Rl -monoids. Also, we give some characterizations of subtractive derivations on the Gödel center. Moreover, Gödel algebras are characterized by a fixed set of subtractive derivations. Finally, we discuss the relationship between subtractive derivations and other derivations for Rl -monoids. These results of the paper can provide the common properties of subtractive derivations in the t -norm-based fuzzy logical algebras.